2020
DOI: 10.3233/jad-191323
|View full text |Cite
|
Sign up to set email alerts
|

Serial Reaction Time Task Performance in Older Adults with Neuropsychologically Defined Mild Cognitive Impairment

Abstract: Background: Studies have found that individuals with mild cognitive impairment (MCI) exhibit a range of deficits outside the realm of primary explicit memory, yet the role of response speed and implicit learning in older adults with MCI have not been established. Objective: The current study aims to explore and document response speed and implicit learning in older adults with neuropsychologically defined MCI using a simple serial reaction (SRT) task. In addition, the study aims to explore the feasibility of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…VIM-DBS is a well-established treatment for tremor in pharmacoresistant ET (Cury et al, 2017). Motor learning deficits have been observed in ET patients (Kronenbuerger et al, 2007;Shill et al, 2009), and the RTs here are slower than in an SRTT in healthy controls of a similar age (Hong et al, 2020). A modulation in motor sequence learning performance during VIM-DBS therefore has important implications for this treatment option.…”
Section: Discussionmentioning
confidence: 84%
“…VIM-DBS is a well-established treatment for tremor in pharmacoresistant ET (Cury et al, 2017). Motor learning deficits have been observed in ET patients (Kronenbuerger et al, 2007;Shill et al, 2009), and the RTs here are slower than in an SRTT in healthy controls of a similar age (Hong et al, 2020). A modulation in motor sequence learning performance during VIM-DBS therefore has important implications for this treatment option.…”
Section: Discussionmentioning
confidence: 84%
“…Compared to standard neuropsychological tests, cognitive tasks have certain advantages and disadvantages: on the one hand, cognitive tasks are usually limited by a lack of standardized data and/or validation with a large population of participants; on the other hand, cognitive tasks are often based on cutting-edge research hypothesis and may be more sensitive in detecting very specific changes in brain function due to brain disease such as AD (Perry and Hodges, 1999) -which might eventually lead to the development of improved and/or novel neuropsychological tests (or being integrated with existing neuropsychological test battery) that can be used in clinical practice after validation. Machine learning studies have shown that data from certain cognitive tasks may contain useful information to differential AD/MCI patients from healthy controls (Wallert et al, 2018;Valladares-Rodriguez et al, 2019;Hong et al, 2020). Therefore, it is of a high interest to investigate whether a combination of neuropsychological tests and cognitive task(s) may improve machine learningbased classification accuracy in AD (Wallert et al, 2018;He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Those who scored more than 20 out of 30 points on the Mini-Mental State Examination and less than 40 points on UPDRS III were eligible to participate. Note that this includes pwPD that may suffer from light dementia which should not affect implicit motor sequence learning ( Hong et al, 2020 ). In addition, we used a short pre-task test block to ensure that finger-tapping skills required to perform the task were intact.…”
Section: Methodsmentioning
confidence: 99%